DEVELOPMENT OF LEARNING MEDIA PIMCA (PINTAR MEMBACA) TO HELP BEGINNING READING OF GRADE 1 SDN DUNGKEK 1 - Syaihol Hadi; Ratna Novita Punggeti; Nisfil Maghfiroh Meita (Universitas Trunojoyo Madura, 2022)
The aim of the research development is to: 1) Develop Pimca (Pintar Membaca) learning media to help students be able to begin reading; and 2) Know the response of teachers and students to the learning media pimca to help them read the beginning. This research refers to the 4D development model which includes the stages of definition, design, development, and dissemination. This development is only carried from the define stage, design, to the development stage. The instrument used in this research was the media design validation sheet and the feasibility of the material. The results of media design validation get a percentage of 80% of media design experts. The validation of material feasibility gets a percentage of 77% of material feasibility experts and is categorized as very suitable and not revised. The product trial stage results in student responses from 5 students of grade II elementary school as subjects research trials. The results of student responses showed very good criteria, it is 94%. Meanwhile, the results of the teacher's response showed very good criteria, namely 100%. Based on the results of the research, it is concluded that the development of pimca media is suitable for use as a media for playing while learning because it has passed validation and has received good responses from students and teachers.